Long-term results of a post-partum bilateral Garden 4 femoral neck fracture in a young woman with transient osteoporosis treated with closed reduction and internal fixation - Bennani, Mourad; Mouad Guenbdar; Taoufik Cherrad; Hassan Zejjari; Hicham Bousbaa; Jamal Louaste; Larbi Amhajji (International Journal of Research in Orthopaedics, 2023)
Bilateral femoral neck fractures are very rare conditions. In our knowledge, only five cases were reported of bilateral acute femoral neck fracture secondary to transient osteoporosis. The present case is the first with a long-term follow up after treatment with closed reduction and internal fixation. A 32-year-old women was admitted to the emergency orthopedic clinic due to severe pain in both hips and an inability to walk one-day post-partum. Clinical examination revealed bilateral externally rotated legs and X-ray showed bilateral Garden 4 displaced subcapital fracture of the neck of the femur. The patient was operated on urgently by closed reduction and internal fixation. Osteoporosis was found in the measurements of bone mineral density and bisphosphonate with vitamin D medication was started. 6 years after surgery the patient can carry out her daily activities without limitation. His Harris hip score was 97 points/right and 95 points/left; and the X-ray was normal regarding osteoarthritis and avascular necrosis. Internal fixation should be the primary choice for the treatment of a bilateral femoral neck fractures with a high degree of displacement in young adults even with reversible poor bone quality condition such transient osteoporosis.